2018
DOI: 10.1002/nbm.3925
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of large strain properties in calf muscles in vivo using magnetic resonance elastography and spatial modulation of magnetization

Abstract: It is important to measure the large deformation properties of skeletal muscle in vivo in order to understand and model movement and the force-producing capabilities of muscle. As muscle properties are non-linear, an understanding of how the deformation state affects the measured shear moduli is also useful for clinical applications of magnetic resonance elastography (MRE) to muscle disorders. MRE has so far only been used to measure the linear viscoelastic (small strain) properties of muscles. This study aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Recent studies have evaluated spasticity (Beattie et al 2016;Marinelli et al 2017;Carlyle and Mochizuki 2018;Chen et al 2018) using electromyography (Cram and Steger 1983) and imaging techniques that quantify muscle spasticity in clinical practice (Illomei et al 2017). New technologies including magnetic resonance elastography (Creze et al 2018;Tan et al 2018;Nelissen et al 2019;Wang et al 2019) and USE show promising findings for the direct measurement of the mechanical properties of muscles (Brandenburg et al 2014). Furthermore, some studies reported that the symptoms of spasticity gradually develop after a stroke (Burke et al 2013) (Rodrigo et al).…”
Section: Spasticitymentioning
confidence: 99%
“…Recent studies have evaluated spasticity (Beattie et al 2016;Marinelli et al 2017;Carlyle and Mochizuki 2018;Chen et al 2018) using electromyography (Cram and Steger 1983) and imaging techniques that quantify muscle spasticity in clinical practice (Illomei et al 2017). New technologies including magnetic resonance elastography (Creze et al 2018;Tan et al 2018;Nelissen et al 2019;Wang et al 2019) and USE show promising findings for the direct measurement of the mechanical properties of muscles (Brandenburg et al 2014). Furthermore, some studies reported that the symptoms of spasticity gradually develop after a stroke (Burke et al 2013) (Rodrigo et al).…”
Section: Spasticitymentioning
confidence: 99%
“…Physiologically, we are typically interested in the nonlinear behavior over the full range of physiological deformations that a muscle undergoes. There is one recent study that has attempted to measure the nonlinear behavior of skeletal muscle, by conducting MRE at a range of quasi-static stretch levels (84). Another recent study has observed increased shear moduli when muscle is indented to induce damage (68).…”
Section: Magnetic Resonance Elastography Of Skeletal Musclementioning
confidence: 99%
“…As result of this wide variation in methods and the use of relatively small samples in many studies, reported results can differ between research laboratories. Another key concern is that due to the nonlinear mechanical behavior of muscle, the loading state of the muscle can strongly affect the measured properties (68,84). To compare results, it therefore is important to standardize the muscle passive tension, perhaps by ensuring that the muscle is completely slack, and also to ensure that the transducer does not load the muscle.…”
Section: Magnetic Resonance Elastography Of Skeletal Musclementioning
confidence: 99%
“…However, this would require an image orientation such that the muscle fibers are in the imaging plane: this is not always possible especially given that fibers have complex 3D architectures. MR imaging has been employed to map regional muscle or cartilage deformation based on sequences that map voxel displacement (displacement encoded imaging) or voxel velocity [Velocity encoded phase contrast imaging (VE-PC)] or MR tagging to track voxel displacements (Spatial Modulation of Magnetization, SPAMM) (Chan et al, 2017;Malis et al, 2018;Sinha et al, 2018;Tan et al, 2018). In addition, deformation analysis of volumetric morphological images acquired in the relaxed and deformed states have been employed to study strain in the muscle (Pamuk et al, 2016) and in the cartilage (Menon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%